A reassessment of some Asian species of Heterophyllium (Schimp.) Kindb. (Pylaisiadelphaceae, Bryophyta). (2nd January 2019) - Jia, Yu; He, Si
ABSTRACT: Introduction. Heterophyllium albicans Thér., H. henryi Tixier, H. micro-alare (Broth. & Paris) Broth. and H. tonkinense (Broth. & Paris) Broth. were all either poorly known species or known only from the type collections since their inception. Methods. Examination of the type material confirmed that the alar cell structure in these species do not conform to the generic concept of Heterophyllium (Schimp.) Kindb. The study also revealed some new features previously unreported in these species, i.e., the filamentous pseudoparaphyllia, one of the characteristic features of the genus Isopterygium Mitt. Key Results & Conclusions. Three new combinations, Isopterygium albicans (Thér.) Y.Jia & S.He, I. micro-alare (Broth. & Paris) Y.Jia & S.He, and I. tonkinense (Broth. & Paris) Y.Jia & S.He are proposed. Heterophyllium henryi Tixier is treated as a new synonym of Brotherella henonii (Duby) M.Fleisch.